Meningkatkan Kemampuan Literasi Numerasi Siswa Dengan Memanfaatkan Sampah Plastik Kresek Sebagai Media Pembelajaran - Zahara Zahara; Eli Nofriati; Husnidar Husnidar; Zulkarnaini Zulkarnaini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to enhance students’ numeracy literacy skills through the use of plastic bag waste as a learning medium. The research is motivated by students’ low level of numeracy literacy and the limited use of contextual and environmentally friendly instructional media. The study employed a Classroom Action Research (CAR) approach conducted in two cycles, consisting of planning, action implementation, observation, and reflection stages. The research participants were sixth-grade students of SD Negeri 3 Muara Batu. Plastic bag waste was utilized as an instructional aid in literacy activities such as arranging letters and words, as well as in numeracy-related tasks including number arrangement and simple addition exercises. Data were collected through observation, tests, and documentation. The findings indicate an improvement in students’ numeracy literacy skills in the second cycle, particularly in terms of conceptual understanding, arithmetic skills, and active participation during learning activities. The use of plastic bag waste as a learning medium proved effective in creating more engaging and contextual learning experiences while also fostering students’ environmental awareness. Therefore, the integration of recycled materials as learning media can serve as an innovative alternative for improving students’ numeracy literacy skills.